COMPETITIVENESS IN THE GLOBAL MARKETING SYSTEM - Semonenko, A.O. (The actual problems of regional economy development, 2024)
The article is devoted to the study of the place and role of competitiveness in the global marketing system. The purpose of the study is to reveal modern views on the interpretation of competitiveness, to identify the factors that determine its provision in the global market, and to identify the special role of marketing tools in its enhancement. To achieve this goal, various research methods were used, such as analysis, classification, grouping, induction, deduction, and generalization. The results of the study show the importance of competitiveness for enterprises in the global marketing environment. Competitiveness is a key factor in the success of enterprises in the context of growing competition and rapid changes in the market. The analysis shows that maintaining competitiveness allows enterprises not only to survive in the market, but also to actively compete and ensure sustainable development. The competitiveness of an enterprise is determined by its abilities and competence, which can turn into competitive advantages. The author of the article analyzes various aspects of competitiveness, including internal and external factors that affect it. In addition, the results of the study emphasize the role of marketing in ensuring the competitiveness of enterprises. In particular, they show that marketing has become a key element of the struggle for market leadership, which requires enterprises to develop effective marketing strategies aimed at creating and selling products with more attractive advantages than those of competitors. The scientific novelty is determined by an integrated approach to understanding the disclosure of competitiveness, where marketing tools are a key element of a successful strategy. The practical significance of the article is to provide enterprises with the means to understand the importance, analyze and improve their marketing strategies in order to increase competitiveness in the global market. Prospects for further research are a deeper analysis of the relationship between marketing and competitiveness, research of the latest technologies and innovations in marketing, as well as the development of marketing strategies aimed at the global market and ensuring competitive advantages for enterprises.